Correction to : expanding the triangle of U: comparative analysis of the Hirschfeldia incana genome provides insights into chromosomal evolution, phylogenomics and high photosynthesis-related traits - Hoang, Nam V.; Walden, Nora; Caracciolo, Ludovico; Luoni, Sofia Bengoa; Retta, Moges; Li, Run; Wolters, Felicia C.; Woldu, Tina; Becker, Frank F. M.; Verbaarschot, Patrick; Harbinson, Jeremy; Driever, Steven M.; et al. (Annals of botany, 2025)
This is a correction to: Nam V Hoang, Nora Walden, Ludovico Caracciolo, Sofia Bengoa Luoni, Moges Retta, Run Li, Felicia C Wolters, Tina Woldu, Frank F M Becker, Patrick Verbaarschot, Jeremy Harbinson, Steven M Driever, Paul C Struik, Herbert van Amerongen, Dick de Ridder, Mark G M Aarts, M Eric Schranz, Expanding the triangle of U: comparative analysis of the Hirschfeldia incana genome provides insights into chromosomal evolution, phylogenomics and high photosynthesis-related traits, Annals of Botany, 2024;, mcae179, https://doi.org/10.1093/aob/mcae179In the originally published version of the manuscript, there were errors in Table 1 and Figures 2-4. In Table 1, in row for “Number of genes”, column “Hirschfeldia incana v.1.0 (NIJ)” numbers should read: “32 313” instead of: ”32 312”. Table 1 should read:
Gesehen am 14.05.2024